HEAT REGIME IN HEATED PREMISES WITH PLANNED CHANGES OF EXTERNAL AIR TEMPERATURE - R. M Zatsev; E. Yu Golubtsova; M. A. Ryabikova (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2014)
The paper considers a heat regime in heated premises, contains information on calculation of optimum enclosure layer size,  development of mathematical model for analysis of air temperature in the premises, heat flows when heat influence is of arbitrary character and substantiates efficient usage of , analyses mathematical model elaborated, effective use of programmable heat consumption.